The A, C, G, and T of Genome Assembly. - Wajid, Bilal; Sohail, Muhammad U.; Ekti, Ali R.; Serpedin, Erchin (BioMed Research International, 2016)
Genome assembly in its two decades of history has produced significant research, in terms of both biotechnology and computational biology. This contribution delineates sequencing platforms and their characteristics, examines key steps involved in filtering and processing raw data, explains assembly frameworks, and discusses quality statistics for the assessment of the assembled sequence. Furthermore, the paper explores recent Ubuntu-based software environments oriented towards genome assembly as well as some avenues for future research.